Derivation and Physical Meaning of the Schrodinger Equation of a Particle in One Dimensional Space - Joko Krismanto Harianja (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
Research has been carried out to determine the physical meaning and derivation of the Schrodinger equation with the literature study research method. Based on the research results obtained through data processing in the form of information obtained from various literature sources, it can be concluded that the general solution of the Schrodinger equation is a wave function. In general, based on mathematical calculations by applying the technique of solving differential equations to the Schrodinger equation, it can be seen that this equation has many solutions, but not all of these solutions can be said to be functions that meet the wave function criteria. This wave function must be able to interpret the real physical criteria of a particle.